آليات تنظيم إدارة العلاقات العامة في صناعة الجمهور - محمودي, محمد بشير (جامعة الوادي - University of Eloued, 2022)
تُعدّ وظيفة الإدارة والتّنظيم إحدى وظائف العلاقات العامة شأنها شأن الوظائف الأخرى (الوظيفة الإعلاميّة الاتصاليّة- الوظيفة النّفسية الاجتماعية والوظيفة التّنظيمية الإداريّة) ، فالوظيفة الإداريّة التّنظيميّة للعلاقات العامة تقُوم أساسًا على إنجاز أهداف تنظيميّة من مُنطلق الإستغلال الأمثل للإمكانات والموارد المُتاحة للمُنظّمة، وهذه الأخيرة لا تتحقّق إلاّ بــــ"التّنظيم"، قصد اجتذاب واستقطاب أكبر عدد ممكن من جماهير المنظمة سواء كان ذلك على المستوى الجمهور الداخلي (جمهور العاملين)، أو على مستوى الجمهور الخارجي (جمهور المتعالمين) على أساس أنّ العلاقات العامة تعد حلقة وصل بين المنظمة "الإدارة العليا" وجماهيرها "الداخلي والخارجي" قصد كسب ثقة وتأييد الجمهور لها من جهة، وإعطاء صورة حسنة وطيبة عن شخصيّة المنظمة وهويتها من جهة أخرى، وهذا ما سيتم تناوله في هذه الورقة البحثيّة. Abstract: The function of management and organization is one of the functions of public relations, like other functions (the communicative media function - the psychosocial function and the administrative organizational function). By "organization", in order to attract and attract the largest possible number of audiences for the organization, whether it is at the internal audience (the working audience), or at the external audience (the communicative audience) on the basis that public relations are a link between the organization, the "senior management" and its audiences. The "internal and external" aim to gain the public's trust and support on the one hand, and give a good image of the organization's personality and identity on the other hand, and this is what will be addressed in this research paper.
مقال
Keywords: تنظيم ؛ إدارة ؛ اتصال ؛ علاقات عامة ؛ جمهور; to organize ; Administration ; Contact ; Public relations ; The audience